Electromagnetic navigation-guided neuroendoscopic removal of radiation-induced intraforniceal cavernoma as a late complication of medulloblastoma treatment - Liby, Petr; Zamecnik, J; Kyncl, M; Zackova, J; Tichy, M (Child's nervous system, 2017)
INTRODUCTION: Medulloblastoma is the most frequent malignant brain tumour in children. Radiation-induced cavernous haemangiomas (RICHs) are a known late complication of radiation exposure, especially in young children. CASE REPORT: We present a patient who underwent subtotal resection of posterior fossa medulloblastoma with subsequent chemotherapy and radiotherapy at the age of 10 years. A new lesion in the region of the left foramen of Monro appeared 16 years later. Based on the imaging results, metastasis or radiation-induced cavernoma was considered. The lesion had the same appearance on imaging as a rarely published intraventricular cavernoma of the foramen of Monro. Unlike the cavernoma of the foramen of Monro, this lesion was subependymal and intraforniceal. Using electromagnetic navigation and neuroendoscopy, the lesion was completely removed. Histopathological examination revealed a cavernous haemangioma. CONCLUSION: This is a unique case of intraforniceal paraforaminal cavernoma that was successfully removed endoscopically using electromagnetic neuronavigation and without neurological sequelae.
Keywords: dospělí; Female; dítě; kavernózní hemangiom; Electromagnetic neuronavigation; Adult; Intraforniceal cavernoma; ženské pohlaví; nádory vyvolané zářením; lidé; nádory mozečku; Medulloblastoma; Foramen of Monro; Electromagnetic Phenomena; Radiation-induced cavernoma; Cerebellar Neoplasms; elektromagnetické jevy; Medulloblastoma treatment; radioterapie; neuroendoskopie; Neuroendoscopy; meduloblastom; Neoplasms, Radiation-Induced; Neuronavigation; Child; Subependymal; Radiotherapy; Hemangioma, Cavernous; neuronavigace; Humans